IMPLEMENTATION OF DISASTER PREPARED EDUCATION AS AN EFFORT TO IMPROVE SD STUDENTS 'KNOWLEDGE ON DISASTER MITIGATION IN SITIARJO VILLAGE, MALANG SELATAN DISTRICT: IMPLEMENTASI PENDIDIKAN SIAGA BENCANA SEBAGAI UPAYA PENINGKATAN PENGETAHUAN SISWA SD TERHADAP MITIGASI BENCANA DI DESA SITIARJO KABUPATEN MALANG SELATAN - Yuli Yana Djito (Universitas Cokroaminoto Palopo, 2020)
ABSTRAK Disaster is a phenomenon that endangers humans (living things) and disaster is one of the characteristics of the Indonesian State. The area that is the object of our dedication to the implementation of disaster preparedness education is in the South Malang Regency area, precisely in the village of Rowotrate because it is located on the southern coast of the sea where floods often occur. Apart from floods in Malang, earthquakes often occur, although on a small scale. Disasters that often occur in Sitiarjo village. This makes people accustomed to it. Even so, disaster preparedness must be instilled in the community from an early age. Some of the things we do when educating children about disaster preparedness are disaster alert education including story telling, materials, games, and simulations. The results of our activities apart from the knowledge that we provide so that it can be useful for children, we also make plans for earthquake disaster mitigation and maps of flood hazard in the locations we visit. Keywords: disaster, sitiarjo village, and disaster preparedness education